Matakau as Natural Resource Management Customary Law in Maluku - Teng Berlianty (Fakultas Hukum Universitas Mataram, 2022)
The management of natural resources based on local wisdom contains the understanding that natural resource management is based on local wisdom by establishing areas that are used as priotected areas and must be maintained and not exploited and as guardians of forest ecosystems. The purposes of this research were to analyze and examine the shape of Matakau in indigenous law communities in Maluku and the implications of matakau as customary law in maintaining and preserving environmental management in Maluku. This research was a normative juridical research, which conducted on the legal principles, in the sense of the value (norm) of concrete laws and legal systems. The approaches used in research were statute approach and conceptual approach. Matakau (Prohibition sign) is a customary law that applies in almost all islands in the Maluku Province. Matakau can be interpreted as a prohibition to take the results of certain natural resources as an effort to preserve the quality and population of natural biological resources (animal and plants) that should continue to be maintained and preserved as part of the local wisdom of indigenous people in Maluku.